Label-free detection and molecular profiling of exosomes with a nano-plasmonic sensor - Im, Hyungsoon (Nat Biotechnol, 2014)
Exosomes show potential for cancer diagnostics because they transport molecular contents of the cells from which they originate. Detection and molecular profiling of exosomes is technically challenging and often requires extensive sample purification and labeling. Here we describe a label-free, high-throughput approach for quantitative analyses of exosomes. Our nano-plasmonic exosome (nPLEX) assay is based on transmission surface plasmon resonance through periodic nanohole arrays. Each array is functionalized with antibodies to enable profiling of exosome surface proteins and proteins present in exosome lysates. We show that this approach offers improved sensitivity over previous methods, enables portable operation when integrated with miniaturized optics and allows retrieval of exosomes for further study. Using nPLEX to analyze ascites samples from ovarian cancer patients, we find that exosomes derived from ovarian cancer cells can be identified by their expression of CD24 and EpCAM, suggesting the potential of exosomes for diagnostics.